2022
DOI: 10.1128/mbio.02187-22
|View full text |Cite
|
Sign up to set email alerts
|

Malic Enzyme, not Malate Dehydrogenase, Mainly Oxidizes Malate That Originates from the Tricarboxylic Acid Cycle in Cyanobacteria

Abstract: Oxygenic photoautotrophic bacteria, namely, cyanobacteria, have the tricarboxylic acid (TCA) cycle. Recently, metabolite production using the cyanobacterial TCA cycle has been well studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, S. elongatus PCC 11802 exhibited considerable flux through MDH, indicating MDH may be the primary route of malate oxidation in this strain (Figure 4). It was previously reported that ME and not MDH is responsible for the oxidation of malate originating from the TCA cycle (Katayama et al., 2022). Thus, the substantial MDH flux deserves further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, S. elongatus PCC 11802 exhibited considerable flux through MDH, indicating MDH may be the primary route of malate oxidation in this strain (Figure 4). It was previously reported that ME and not MDH is responsible for the oxidation of malate originating from the TCA cycle (Katayama et al., 2022). Thus, the substantial MDH flux deserves further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…In a previous study, Pyk from Synechocystis demonstrated a higher Pyk activity under heterotrophic conditions than under photoautotrophic and mixotrophic conditions (Knowles and Plaxton 2003 ). Recently, ME, which generates pyruvate from malate by the ME-dependent TCA cycle, was reportedly active under photoautotrophic conditions (Katayama et al 2022 ), indicating that pyruvate is synthesized by ME and not by Pyk (Bricker et al 2004 ; Qian et al 2018 ). The pathway involving PEPC, MDH, and ME constitutes an alternate route for pyruvate formation in Synechocystis cells under photosynthetic conditions (You et al 2014 ; Bricker et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Synechocystis has a unique tricarboxylic acid (TCA) cycle lacking 2-oxoglutarate dehydrogenase and possessing alternative pathways, such as a γ-butyric amino acid (GABA) shunt (Zhang and Bryant 2011 ; Xiong et al 2014 ). The properties of the enzymes of the Synechocystis TCA cycle have been studied, including those of citrate synthase (CS encoded by gltA , sll0401) (Ito et al 2019 ), aconitase (Aco encoded by acnB , slr0665) (Nishii et al 2021 ; de Alvarenga et al 2020 ), isocitrate dehydrogenase (IDH encoded by icd , slr1289) (Muro-Pastor and Florencio 1992 ), malate dehydrogenase (MDH encoded by citH , sll0891) (Takeya et al 2018 ), malic enzyme (ME encoded by me , sll0721) (Katayama et al 2022 ), and succinate dehydrogenase (SDH encoded by sdh , sll0823 and sll1625) (Cooley and Vermaas 2001 ). Two enzymes, phosphoenolpyruvate carboxylase (PEPC) and pyruvate kinase (Pyk), catalyze specific reactions that provide carbon sources to the TCA cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hydrogenase-produced H 2 is diffusive and thus difficult to store and reuse as reducing power when cells return to aerobic conditions. Unlike hydrogen fermentation, the reverse tricarboxylic acid (rTCA) cycle produces dicarboxylic acids, which are reusable for generating NADPH via the TCA cycle under aerobic conditions (32). However, adding bicarbonate to phosphoenolpyruvate (PEP) is a rate-limiting step in the rTCA cycle (33).…”
Section: Discussionmentioning
confidence: 99%
“…Another significance for transient upregulation may be the reusability of fermentative products. Hydrogen, lactate, and dicarboxylic acids can be reused as the source of reducing power when cells return to aerobic conditions (12, 35, 36). The substrate proton is abundant, but hydrogen is diffusive and difficult to store.…”
Section: Discussionmentioning
confidence: 99%